A participatory soil quality assessment in Northern Ethiopia's Mai-Negus catchment - Brhane Tesfahunegn, Gebrayesus; Tamene, Lulseged D.; Vlek, Paul L.G. (Elsevier, 2011)
Local communities often have substantial knowledge related to trends in soil quality and the associated limiting factors. Despite this, soil quality (SQ) degradation is a critical problem in Ethiopia and there is little or insufficient scientific information documenting local community experience in assessing SQ. This paper presents experiences of local communities in diagnosis of SQ and assesses the contribution of local knowledge as a strategy for sustainable development decision making within the Mai-Negus catchment of northern Ethiopia. Participatory transect-walks, group discussions and field observation which complemented by household interview were used to acquire data. Farmers identified SQ indicators e.g., crop yield, soil depth, erosion and sedimentation as their basis of categorizing the soils into high, medium and low SQ. They were also able to identify severely degraded areas (hotspots) and underlying causes. Significant variations (P ? 0.05) were shown between the proportions of farmers used certain SQ indicator and those who didn't while categorizing SQ. Local farmers involved in this study demonstrated their capability to suggest appropriate land management solutions for specific problems. This study demonstrates the benefit of involving local farmers in both problem identification and solution development so that anti-degradation technologies can easily be implemented and adopted.